Pigeon geographies: aesthetics, organisation, and athleticism in British pigeon fancying, c.1850-1939 - Whiston, Kate (2017)
This thesis provides new ways of thinking about human-bird encounters under domestication, providing the first substantive geographical study of ‘pigeon geographies’. It explores the spaces, practices, and human-pigeon relationships involved in pigeon showing and long-distance pigeon racing in Britain, from the mid-nineteenth century up until World War Two. The growth of fancy pigeon exhibitions was part of a wider Victorian passion for domesticating animals, at a time when human bodies were also subject to increasing aesthetic and moral scrutiny. Long-distance pigeon racing emerged at the end of this period, organised competitive sport more generally seen as an important means of moral improvement and identity expression. Like many other competitive pastimes in the second half of the nineteenth century, then, institutional bodies were formed to manage the expansion of showing and long-distance racing. The Pigeon Club and the Marking Conference were formed in 1885 to oversee British pigeon exhibitions, whilst the National Homing Union, formed in 1896, governed British long-distance pigeon racing. Both pastimes facilitated the formation of social worlds around varieties of domestic pigeon (Columba livia) and their respective practices. Whilst these pastimes historically had strong concentrations of male working-class followers – particularly in the north-west and north-east – they were both widespread throughout Britain and spanned all socio-economic classes, although accounts of female fanciers were rare.